CRISPR/Cas9 mediated G4946E substitution in the ryanodine receptor of Spodoptera exigua confers high levels of resistance to diamide insecticides - Zuo, Yayun; Wang, Hui; Xu, Yanjun; Huang, Jianlei; Wu, Shuwen; Wu, Yidong; Yang, Yihua (Insect biochemistry and molecular biology, 2017)
Diamide insecticides selectively activate insect ryanodine receptors (RyRs), inducing uncontrolled release of calcium ions, and causing muscle contraction, paralysis and eventually death. The RyRG4946E substitution associated with diamide resistance has been identified in three lepidopteran pests, Plutella xylostella, Tuta absoluta and Chilo suppressalis. Recently, the T. absoluta RyRG4946V mutation was knocked into the model insect Drosophila melanogaster by CRISPR/Cas9 mediated genome editing and provided in vivo functional confirmation for its role in diamide resistance. In the present study, we successfully introduced the RyRG4946E mutation with CRISPR/Cas9 technology into a lepidopteran pest of global importance, Spodoptera exigua. The genome-edited strain (named 4946E) homozygous for the SeRyRG4946E mutation exhibited 223-, 336- and >1000-fold resistance to chlorantraniliprole, cyantraniliprole and flubendiamide, respectively when compared to the wild type strain (WHS) of S. exigua. Reciprocal crossing experiments revealed that the target-site resistance in strain 4946E underlies an autosomal and almost recessive mode of inheritance for anthranilic diamides, whereas it was completely recessive for flubendiamide. Our results not only provided in vivo functional validation of the RyRG4946E mutation in conferring high levels of resistance to diamide insecticides for the first time in a controlled genetic background of a lepidopteran pest, but also revealed slight differences on the level of resistance between anthranilic diamides (chlorantraniliprole and cyantraniliprole) and flubendiamide conferred by the SeRyRG4946E mutation. [Display omitted] •Diamide insecticides target insect ryanodine receptors (RyRs).•The RyRG4946E substitution associated with diamide resistance identified in three lepidopteran pests.•The RyRG4946E mutation was introduced with CRISPR/Cas9 into a lepidopteran pest Spodoptera exigua.•The S. exigua strain with the SeRyRG4946E mutation confers high levels of resistance to diamides.